Comparison Between Transcutaneous and Total Serum Bilirubin Measurement in Malay Neonates - Mohamed, Mazrah (2021)
Background: Transcutaneous bilirubinometer is a portable, painless and non-invasive device to measure bilirubin. This study aims to investigate the reliability of Dräger Jaundice Meter JM-105 for the screening of neonatal jaundice in Malay neonates. Methods: Prospective cross-sectional study conducted in a tertiary university hospital involving 130 jaundiced neonates who required serum bilirubin determination from day 2 to day 7 of life. Paired bilirubin samples of total serum bilirubin (TSB) and transcutaneous bilirubin (TcB) were obtained. TcB were measured at the neonates’ forehead and sternum. The TcB were measured using JM-105. Results: There were 130 paired samples of TSB and TcB. The mean TSB was 232 μmol/L. The mean TcB measured at forehead and sternum were 222 μmol/L and 223 μmol/L, respectively. The mean difference between TSB and TcB was 10 μmol/L at forehead and 9 μmol/L at sternum. Strong positive correlation between TSB with mean TcB forehead (r=0.82) and TcB sternum (r=0.80), and strong correlation (r=0.91) between TcB forehead and TcB sternum. Conclusion: Our study demonstrated strong correlation between TcB values and TSB values. TcB measured at forehead or sternum is a good alternative as a non-invasive screening tool for non-severe hyperbilirubinemia in Malay neonates.